High-safety solid-state lithium metal battery and preparation method thereof

By constructing a heterogeneous interface layer between the lithium metal negative electrode and the solid electrolyte, the thermal runaway and interface reaction instability problems in solid lithium metal batteries under high temperature and high current density conditions are solved, and the safety, cycle life and stability performance of the battery are significantly improved.

CN119674257AActive Publication Date: 2025-03-21NANJING UNIV OF AERONAUTICS & ASTRONAUTICS

Patent Information

Application Number
CN202411854238.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Solid-state lithium metal batteries have problems with thermal runaway, lithium dendrites growth and interface reaction instability under high temperature and high current density conditions, resulting in insufficient safety and cycle life.

Method used

A heterogeneous interface layer is constructed between the lithium metal negative electrode and the solid electrolyte, and a bilayer composite structure composed of passivation layer and polymer/semiconductor, including alumina and amorphous silicon layers. By precisely controlling the composition and thickness of the interface layer, interface contact and chemical stability are improved.

Benefits of technology

It effectively inhibits the growth and interface reaction of lithium dendrites, significantly improves the thermal stability and chemical stability of the battery, extends the cycle life, and maintains high safety and stable performance under high temperature and high current density conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674257A_ABST
    Figure CN119674257A_ABST
Patent Text Reader

Abstract

The invention discloses a high-safety solid-state lithium metal battery which comprises a negative electrode, a solid-state electrolyte and a positive electrode and further comprises a heterogeneous interface layer located between the negative electrode and the solid-state electrolyte, and the heterogeneous interface layer is of a double-layer composite structure composed of a passivation layer and a polymer / semiconductor. The passivation layer is at least one of a nitride layer, an oxide layer, a nitrogen chemical layer, a carbon-based layer, a phosphate layer, a fluoride layer and a metal-based protection layer. The heterogeneous interface layer is introduced between the lithium metal negative electrode and the solid electrolyte, so that the physical contact between the lithium metal negative electrode and the solid electrolyte can be effectively improved, the growth of lithium dendrites can be prevented, the interface reaction between the lithium metal and the solid electrolyte can be reduced, and the problem of fire and combustion caused by thermal runaway at high temperature can be effectively inhibited; and the stability, safety and cycle performance of the solid-state lithium metal battery at room temperature and high temperature are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, in particular to a highly safe solid-state lithium metal battery and a method for preparing the same. Specifically, the present invention provides a technical solution for improving the safety, thermal stability and cycle life of a lithium metal battery by constructing a heterogeneous interface layer. Background Art

[0002] With the rapid development of global energy transformation and new energy vehicle industry, battery technology, especially in improving battery safety and energy density, has become an important direction of global scientific and technological innovation. Solid-state lithium batteries are widely regarded as a strong competitor for the next generation of battery technology due to their higher energy density and better safety.

[0003] At present, the rapid development of solid-state battery technology is driven by the needs of new energy vehicles, grid energy storage and other fields. Many companies have disclosed product development progress and mass production plans. For example, EVE Energy plans to launch solid-state batteries for hybrid power in 2026, GAC Group announced that its self-developed solid-state battery technology has made a breakthrough, and CATL is also promoting the research and development of solid-state batteries, planning small-scale mass production in 2027. China is accelerating the industrialization process in the field of solid-state batteries, committed to meeting the growing market demand for new energy vehicles and other application fields.

[0004] Although solid-state lithium batteries have many advantages in theory, they still face some technical bottlenecks, especially the problem of interface stability between lithium metal anode and solid electrolyte. Due to its high energy density, lithium metal anode is easy to react with solid electrolyte during use, resulting in increased interface resistance and inducing lithium dendrite growth, which in turn affects the overall performance of the battery and may cause thermal runaway under extreme conditions. Especially under high current density and high temperature environment, the interface contact between solid electrolyte and electrode is poor, and the instability of chemical and electrochemical reactions is aggravated, which greatly increases the risk of thermal runaway of the battery, thereby accelerating the thermal degradation of the electrolyte, and ultimately leading to a sharp decline in battery performance, and even safety accidents such as short circuit and explosion.

[0005] In order to solve these problems in the prior art, existing research has focused on improving the interface stability between the electrode and the solid electrolyte by introducing a protective layer (such as fluoride or oxide). However, the inventor has found that there is a public technology that attempts to suppress the growth of lithium dendrites and improve the cycle life of the battery by introducing a metal grid skeleton, including a composite of a lithium metal negative electrode and a metal grid skeleton, and a passivation film layer (such as LiCl or LiF film). This method focuses more on suppressing the growth of lithium dendrites. Although the metal grid skeleton can improve the deposition uniformity of lithium metal, its role is limited to physical support, and the improvement of the chemical stability of the interface is limited, especially under high temperature conditions. At present, there are also single-layer interface modification materials such as fluorides or oxides. This type of passivation film reduces the side reactions of the interface to a certain extent, but it cannot buffer the volume change of lithium metal. Under high current density or high temperature environment, its ability to suppress lithium dendrites and interface stability are still insufficient. Similarly, the effect of improving thermal stability under high temperature conditions is limited, and it still cannot effectively solve safety problems such as fire and combustion caused by thermal runaway.

[0006] Therefore, most of the above existing technology methods rely on a single interface layer and cannot effectively meet the requirements of stability under extreme environments such as high temperature, low resistance and long life under high current density. The existing technology still has great limitations when facing safety and stability issues under extreme conditions such as high temperature.

[0007] In summary, it is urgent to overcome the many technical difficulties existing in the above-mentioned existing technologies. Summary of the invention

[0008] In response to the above-mentioned problems existing in the prior art, the present application improves the high safety and stability of the solid-state lithium metal battery by constructing a heterogeneous interface layer in the structure, effectively inhibits interface reactions and thermal runaway phenomena, and improves the safety, cycle life and stability performance of the prior art batteries under extreme conditions.

[0009] The present application provides a highly safe solid-state lithium metal battery, comprising a lithium metal negative electrode, a solid electrolyte and a positive electrode, characterized in that: it also comprises a heterogeneous interface layer located between the negative electrode and the solid electrolyte, wherein the heterogeneous interface layer is a double-layer composite structure consisting of a passivation layer and a polymer / semiconductor, wherein the passivation layer includes but is not limited to one of a nitride layer, an oxide layer, a nitrogen chemical layer, a carbon-based layer, a phosphate layer, a fluoride layer and a metal-based protective layer; the semiconductor includes but is not limited to Si, Ge or their composite alloys.

[0010] Preferably, the heterogeneous interface layer is located between the lithium metal negative electrode and the solid electrolyte.

[0011] Preferably, the metal-based protective layer is made of metal In, Sn, Ti, Al or their alloy materials.

[0012] Preferably, the solid electrolyte is, but is not limited to, Li 1.5 Al 0.5 Ge 1.5 (PO4)3 (LAGP), Li 1.3 AI O.3 Ti 1.7 (PO4)3 (LATP), Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 (LLTO), Li7La3Zr2O 12 (LLZO) and other oxide solid electrolytes, which have excellent ionic conductivity and chemical stability.

[0013] The present invention also provides a method for preparing a high-safety solid-state lithium metal battery, which is characterized by comprising the following steps: Step 1: Synthesize solid electrolyte The oxide layer solid electrolyte is synthesized by conventional solid-state reaction method; The second step is to prepare the heterogeneous interface layer First, a passivation layer is deposited on the surface of the solid electrolyte using atomic layer deposition (ALD) technology; Subsequently, a layer of polymer / semiconductor is deposited on the passivation layer by magnetron sputtering, spin coating or plasma enhanced chemical vapor deposition (PECVD) technology to form a heterogeneous interface layer; Step 3: Preparation of ionic liquid Mixing lithium salt, potassium salt and cesium salt in a predetermined ratio and heating them until they are melted to form an ionic liquid; Step 4: Prepare the positive electrode Ru nanoparticles were directly assembled on a carbon fiber substrate by direct current reactive magnetron sputtering technology, and ionic liquid was added between the positive electrode and the solid electrolyte to improve the contact between the electrode and the solid electrolyte; Step 5: Battery Assembly The battery is assembled with a lithium metal anode, a solid electrolyte containing a heterogeneous interface layer, and a Ru cathode.

[0014] Preferably, the thickness of the passivation layer is 1-10 nm, and the thickness of the polymer / semiconductor layer is 50-200 nm. Further preferably, the thickness of the aluminum oxide is 6-7 nm, and the thickness of the amorphous silicon is 60-70 nm.

[0015] The present invention also provides an application of the above-mentioned high-safety solid-state lithium metal battery, which is suitable for a variety of solid electrolyte materials and can work stably under high temperature and high current density conditions, providing a high-energy density safety solution for electric vehicles, energy storage systems, aerospace, military equipment, deep-sea exploration and other fields.

[0016] The technical solution provided by this application has at least the following technical effects or advantages: 1. The present invention can effectively improve the physical contact between the lithium metal negative electrode and the solid electrolyte by introducing a heterogeneous interface layer between the lithium metal negative electrode and the solid electrolyte, prevent the growth of lithium dendrites, and reduce the interface reaction between lithium metal and the solid electrolyte, effectively suppress the problem of thermal runaway and fire at high temperature, and enhance the stability, safety and cycle performance of solid-state lithium metal batteries at room temperature and high temperature.

[0017] 2. The present invention not only solves the interface stability problem in the prior art by precisely controlling the composition and thickness of the heterogeneous interface layer, but also significantly improves the overall performance of the battery at high temperature and high current density, significantly improves the cycle life of the battery, and solves the problem that traditional batteries are easily degraded under high current density and high temperature environments; compared with the single interface layer solution in the prior art, the heterogeneous interface layer of the present invention has higher and better thermal stability and chemical stability, improves the charge and discharge capacity of the battery at high current density, significantly improves the rate performance of the battery, and provides a more reliable technical guarantee for the high safety and high efficiency of solid-state lithium batteries.

[0018] 3. The present invention is applicable to a variety of solid electrolyte materials, including oxides, sulfides, phosphates, polymers, fluorides, nitrides and halides, and can provide extensive technical support for different types of battery applications.

[0019] 4. The battery of the present invention is particularly suitable for stable operation under high temperature conditions above 150°C, and is suitable for electric vehicles, energy storage systems, aerospace, military equipment and other fields.

[0020] 5. The solid-state lithium metal battery of the present invention can not only provide high energy density and excellent performance under normal temperature conditions, but also can work continuously and stably under extreme conditions (such as high temperature environment or high current density), and has important practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the structure of a solid-state lithium metal battery in an embodiment of the present invention.

[0022] Figure 2 This is a flow chart for preparing the silicon-based heterogeneous interface layer of the solid-state lithium battery in an embodiment of the present invention and the SEM images of LAGP after each process.

[0023] Figure 3 This is a comparison diagram of high-temperature thermal runaway experiments before and after the introduction of the heterogeneous interface layer into the LAGP solid electrolyte in an embodiment of the present invention. DETAILED DESCRIPTION

[0024] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods. Example

[0025] This embodiment provides a highly safe solid-state lithium metal battery, such as Figure 1 As shown, including: Lithium metal negative electrode Li: As the negative electrode of the battery, it provides lithium ions and has a high energy density.

[0026] Oxide solid electrolytes SSEs: As a transport medium for lithium ions, they have good ionic conductivity and chemical stability, and are suitable for stable operation under high temperature and high current density conditions.

[0027] Heterogeneous interface layer: Located between the lithium metal negative electrode and the solid electrolyte, it uses a combination of aluminum oxide (Al2O3) and amorphous silicon (a-Si) layers to optimize interface contact, inhibit side reactions, and effectively prevent thermal runaway at high temperatures. Aluminum oxide, as a passivation material, forms LiAlO2 during the charge and discharge process. This is a fast ion conductor with a high lithium ion diffusion coefficient that can promote the insertion and deintercalation of lithium ions. During the charge and discharge process, LiAlO2 ion channels can be formed, thereby improving the transport characteristics of lithium ions. The formation of this ion channel helps to improve the charge and discharge efficiency and cycle stability of the battery. Amorphous Si directly contacts Li and can form Li x Si alloy, the formation of this alloy improves solid-solid contact and improves the conductivity of the battery. At the same time, because Si does not react with Li, it also isolates the oxygen generated by the direct contact between Li and LAGP at high temperature, thereby preventing possible thermal runaway. Through the design of the above-mentioned heterogeneous interface layer, the present invention effectively optimizes the interface contact between the lithium metal negative electrode and the solid electrolyte, inhibits the occurrence of side reactions, and effectively avoids the growth of lithium dendrites.

[0028] The heterogeneous interface layer in this embodiment is a double-layer composite structure composed of aluminum oxide Al2O3 and amorphous silicon a-Si, wherein the thickness of aluminum oxide is 6nm and the thickness of amorphous silicon is 70nm. The heterogeneous interface in this embodiment can effectively prevent thermal runaway caused by interface reaction.

[0029] This embodiment also discloses a method for preparing the solid-state lithium metal battery, comprising the following steps: Step 1: Synthesis of solid electrolyte (LAGP) 1) Raw material preparation: First, Li2CO3 (99%, Alfa Aesar), Al2O3 (99%, Aladdin), NH4H2PO4 (AR, Nanjing Chemical Reagent Co., Ltd.), and GeO2 (99.999%, Sinopharm Chemical Reagent, Beijing) were mixed in proportion to obtain a uniform powder.

[0030] 2) Ball milling: Place the mixed powder into a high-energy ball mill, set the ball milling speed to 400 rpm, and the ball milling time to 4.5 hours to ensure that the raw materials are fully mixed.

[0031] 3) Sintering process: The milled mixture powder is placed in a muffle furnace, sintered at 600 °C for 1 hour, ball-milled again at 400 rpm for 4.5 hours, and then sintered at 900 °C for 6 hours. The sintered powder is ball-milled again for 4 hours to ensure its uniformity.

[0032] 4) Pressing and final sintering: The obtained powder is pressed into a disc with a diameter of 18 mm and a thickness of 0.9 mm, and then sintered at 900 °C for 6 hours to finally obtain the desired LAGP solid electrolyte sheet.

[0033] The second step is the preparation of the heterogeneous interface layer. Figure 2 As shown: 1) Deposition of aluminum oxide layer: Using atomic layer deposition (ALD) technology, an Al2O3 layer with a thickness of about 6 nm is deposited on the surface of the obtained LAGP to improve the interface stability.

[0034] 2) Deposition of amorphous silicon layer: An amorphous silicon (a-Si) layer with a thickness of about 70 nm is deposited on the Al2O3 layer by plasma enhanced chemical vapor deposition (PECVD) technology to form a heterogeneous interface layer with high ionic conductivity, effectively avoiding thermal runaway.

[0035] Step 3: Preparation of ionic liquids Lithium nitrate with a purity of 99.99%, potassium nitrite with a purity of 99.99%, and cesium nitrate with a molar ratio of 37:39:24 are mixed, and heated to 120° C. until the mixture is completely melted to obtain the desired ionic liquid.

[0036] Step 4: Preparation of positive electrode Ru nanoparticles were deposited on the carbon fiber substrate using a DC reactive magnetron sputtering technique with a sputtering time of 0.5 to 3 min, an operating pressure of 0.2 Pa, a power of 100 W, and a current density of 0.3 A.

[0037] After the positive electrode was prepared, 20 μl of the ionic liquid was added between the solid electrolyte and the positive electrode using a pipette to ensure good contact between the electrolyte and the electrode.

[0038] Step 5: Battery Assembly The lithium metal anode, the solid electrolyte containing the heterogeneous interface layer and the Ru cathode are assembled into a battery. The battery packaging adopts standard battery packaging technology to ensure that the battery will not leak due to temperature changes or other external factors during use.

[0039] In the preparation process of the battery in this embodiment, the thickness and composition of the heterogeneous interface layer can be precisely controlled by combining the atomic layer deposition (ALD) technology with the plasma enhanced chemical vapor deposition (PECVD) technology, making the interface layer more uniform and having lower conductivity loss. This sophisticated preparation process can ensure that the battery will not experience performance degradation caused by interface instability during long-term use, improve the thermal stability of the battery, inhibit the growth of lithium dendrites and significantly extend the cycle life of the battery.

[0040] like Figure 3 As shown, a thermal runaway experiment was carried out at 260°C in an inert gas atmosphere on the solid electrolyte before and after the introduction of the heterogeneous interface layer, which specifically demonstrated the improvement of the stability of the battery in an extremely high temperature environment after the introduction of the heterogeneous interface layer.

[0041] The above experimental results show that the present invention successfully prepares a solid-state lithium metal battery with high safety and stability, and the introduced heterogeneous interface layer significantly improves the cycle stability of the battery.

[0042] Specifically, through testing, the Li symmetric battery with the same method introducing the heterogeneous interface layer has a power consumption of 0.1 mA cm at room temperature. -2 The battery cycle life was significantly improved by the introduction of the heterogeneous interface layer. In addition, the Li-CO2 battery with the heterogeneous interface layer had a cycle life of more than 560 hours at a current density of 500 mA g at 150 °C. -1 The current density and 500 mAh g -1 Under the capacity limitation of , it can stably cycle for more than 150 cycles, demonstrating extremely excellent high-temperature performance and the universality of the heterogeneous interface layer.

[0043] The comparative experiments show that the innovative heterogeneous interface layer design not only significantly improves the safety, stability and high temperature adaptability of the battery, but also increases the battery life and cycle performance. The experimental results verify the effectiveness of the present invention, especially in terms of high temperature stability and cycle life.

[0044] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements without departing from the principle of the present invention. These improvements should also be regarded as within the scope of protection of the present invention.

Claims

1. A highly safe solid-state lithium metal battery, comprising a lithium metal negative electrode, a solid electrolyte and a positive electrode, characterized in that: It also includes a heterogeneous interface layer located between the negative electrode and the solid electrolyte, wherein the heterogeneous interface layer is a double-layer composite structure consisting of a passivation layer and a polymer / semiconductor layer, wherein the passivation layer is at least one of a nitride layer, an oxide layer, a nitrogen chemical layer, a carbon-based layer, a phosphate layer, a fluoride layer and a metal-based protective layer, wherein the thickness of the passivation layer is 1 to 10 nm, and the thickness of the polymer / semiconductor layer is 50 to 200 nm.

2. The highly safe solid-state lithium metal battery according to claim 1, characterized in that: The heterogeneous interface layer is located between the lithium metal negative electrode and the solid electrolyte.

3. The highly safe solid-state lithium metal battery according to claim 2, characterized in that: The passivation layer is aluminum oxide, and the semiconductor layer is amorphous silicon.

4. The highly safe solid-state lithium metal battery according to claim 3, characterized in that: The thickness of the aluminum oxide is 6-7 nm, and the thickness of the amorphous silicon is 60-70 nm.

5. The highly safe solid-state lithium metal battery according to claim 1, characterized in that: The metal-based protective layer is made of metal In, Sn, Ti, Al or their alloy materials.

6. The highly safe solid-state lithium metal battery according to claim 1, characterized in that: The solid electrolyte is LAGP, LATP, LLTO or LLZO oxide solid electrolyte.

7. A method for preparing a highly safe solid-state lithium metal battery, characterized in that: The steps include: Step 1: Synthesize solid electrolyte The oxide solid electrolyte is synthesized by conventional solid-state reaction method; The second step is to prepare the heterogeneous interface layer First, a passivation layer is deposited on the surface of the solid electrolyte using atomic layer deposition (ALD) technology; Subsequently, a layer of polymer / semiconductor is deposited on the passivation layer by magnetron sputtering, spin coating or plasma enhanced chemical vapor deposition (PECVD) technology to form a heterogeneous interface layer; Step 3: Preparation of ionic liquid Mixing lithium salt, potassium salt and cesium salt in a predetermined ratio and heating them until they are melted to form an ionic liquid; Step 4: Prepare the positive electrode Ru nanoparticles were directly assembled on a carbon fiber substrate by direct current reactive magnetron sputtering technology, and ionic liquid was added between the positive electrode and the solid electrolyte to improve the contact between the electrode and the solid electrolyte; Step 5: Battery Assembly The battery is assembled with a lithium metal anode, a solid electrolyte containing a heterogeneous interface layer, and a Ru cathode.

8. The method for preparing a highly safe solid-state lithium metal battery according to claim 7, characterized in that: The passivation layer is at least one of a nitride layer, an oxide layer, a nitrogen chemical layer, a carbon-based layer, a phosphate layer, a fluoride layer and a metal-based protective layer; the polymer / semiconductor layer is Si, Ge or a composite alloy thereof.

9. The method for preparing a highly safe solid-state lithium metal battery according to claim 7, characterized in that: The heterogeneous interface layer is an aluminum oxide layer in contact with the solid electrolyte, and is an amorphous silicon layer in contact with the negative electrode; the aluminum oxide has a thickness of 1-10 nm, and the amorphous silicon has a thickness of 50-200 nm.

10. An application of a highly safe solid-state lithium metal battery as claimed in claim 1 or 7, characterized in that: The battery is suitable for electric vehicles, energy storage systems, aerospace, military equipment and deep-sea exploration.

Citation Information

Patent Citations

  • Lithium / garnet-based solid electrolyte interface with low interface impedance and preparation method of solid electrolyte interface

    CN113381055A

  • Interface layer for high-temperature solid lithium metal and preparation method

    CN113422103A

  • Preparation method of interface between composite metal lithium electrode and solid electrolyte

    CN113690408A

  • Multilayer composite solid electrolyte and preparation method thereof

    CN114156532A

  • Preparation method of LATP-based solid electrolyte interface layer and preparation method of LATP-based solid lithium battery

    CN114883641A

Cited By

  • High-safety lithium metal battery and preparation method thereof

    CN120637564A

  • Preparation method of modified LATP solid electrolyte based on ion implantation technology

    CN122418020A